Effectiveness of Eye Movement Desensitization and Reprocessing (EMDR) Therapy on Fear of Cancer Recurrence and Body Image in Patients with Breast Cancer - Shojaei, Azita; Vatankhah, Hamidreza; Abolghasemi, Shahnam (Psychology of Woman Journal, 2025)
Objective: The present study aimed to compare the effectiveness of Eye Movement Desensitization and Reprocessing (EMDR) therapy on fear of cancer recurrence and body image in patients with breast cancer.Methods and Materials: This research employed a quasi-experimental design, using a pretest-posttest-follow-up model with a control group for data collection. The statistical population consisted of women undergoing chemotherapy for breast cancer who visited the Jihad Daneshgahi Breast Disease Specialized and Subspecialized Clinic in Tehran during the second half of 2023. From this population, 40 individuals were selected using cluster random sampling and were randomly assigned to an experimental group (n = 20) and a control group (n = 20). The experimental group received EMDR therapy across eight 90-minute sessions, while the control group was placed on a waiting list. The research instruments included the Fear of Cancer Recurrence Inventory (Simard & Savard, 2009) and the Body Image Scale (Cash, 1994). Data analysis was conducted using SPSS version 27 in two phases: descriptive and inferential statistics (ANCOVA and MANCOVA).Findings: The findings indicated that EMDR therapy had a significant impact on components of fear of cancer recurrence and body image compared to the control group in both the posttest and follow-up phases (P < 0.05).Conclusion: It can be concluded that EMDR therapy, through its specialized techniques, was effective in improving fear of cancer recurrence and body image, and its integration alongside pharmacological treatments is recommended.